Paroxysmal dyspnoea in asthma: Wheeze, ILO or dysfunctional breathing? - Crawford, A. L.; Blakey, J. D.; Baumwol, K. (Frontiers in Allergy, 2022)
Paroxysms of dyspnoea in the general population are commonly reported and are frequently assumed to be asthma-related, especially if this diagnostic label has been previously applied. Often, this is not the case. Inducible Laryngeal Obstruction (ILO) and Dysfunctional Breathing (DB) are common comorbid conditions that go unrecognised in many difficult-to-treat asthmatics. On average, these patients have a delay in diagnosis of almost 5 years. This delay, along with ineffective, inappropriate escalation of asthma therapy, frequent hospital presentations for uncontrolled symptoms, and even intensive care admissions, magnifies patient morbidity and poor quality of life. ILO and DB have similar presentations and triggers to asthma. Differentiating between them can be challenging, especially in centres that do not have access to multidisciplinary subspecialty asthma services. Objectively confirming the diagnosis can likewise be challenging as symptoms fluctuate, and gold-standard investigations require extensive experience. This mini-review will summarise the clinical features of ILO and DB, with particular focus in the context of individuals treated for asthma. This narrative review will define each condition, highlight poignant aspects of the history and describe elements of the diagnostic pathway to gain objective confirmation.